1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4.., 16x^4 + 4x^2 + 1
is there a significance to the .. at the end of the first term?
if not, then
1 + 4x + 4x^2 - 16x^4
= (1+4x) + 4x^2(1 - 4x^2)
= (1 + 4x) + 4x^2(1 - 2x)(1 + 2x)
1 + 2x - 8x^3 - 16x^4
= (1+2x) - 8x^3(1 + 2x^2)
16x^4 + 4x^2 + 1
= (16x^4 + 8x^2 + 1) - 4x^2
= (4x^2 + 1)^2 - 4x^2
= (4x^2 + 1 + 2x)(4x^2 + 1 - 2x)
= (4x^2+2x+1)(4x^2-2x+1)
At the moment I can't see anything else to do with the first two.
Find the HCF and LCM of:
1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4.., 16x^4 + 4x^2 + 1
7 answers
2x^2(x^-a^2);3x^3(x^3-a^3) find lcm
in 2nd exp after taking -8x^3 common there should only be (1+2x)
Find the HCF and LCM of:
1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4..,
1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4..,
First exp=1+4x+4x^2-16x^4
=(1)^2+2.1.2x+(2x)^2-16x^4
=(1+2x)^2-(4x^2)^2
=(1+2x+4x^2) (1+2x-4x^2)
Second exp.=1+2x-8x^3-16x^4
=(1)^3-(2x)^3+2x-16x^4
=(1-2x)(1+2x+4x^2)+2x(1-8x^3)
=(1+2x)(1-2x)(1+2x+4x^2)
:HCF=(1+2x+4x^2)
=(1)^2+2.1.2x+(2x)^2-16x^4
=(1+2x)^2-(4x^2)^2
=(1+2x+4x^2) (1+2x-4x^2)
Second exp.=1+2x-8x^3-16x^4
=(1)^3-(2x)^3+2x-16x^4
=(1-2x)(1+2x+4x^2)+2x(1-8x^3)
=(1+2x)(1-2x)(1+2x+4x^2)
:HCF=(1+2x+4x^2)
1+2x+4x^2
The HCF of the first two expressions is indeed:
$1 + 4x + 4x^2 - 16x^4 = (1 + 2x)(1 - 2x + 4x^2)$
$1 + 2x - 8x^3 - 16x^4 = (1 + 2x)(1 - 2x + 4x^2) - 8x^3$
Therefore, the HCF is $1 - 2x + 4x^2$.
$1 + 4x + 4x^2 - 16x^4 = (1 + 2x)(1 - 2x + 4x^2)$
$1 + 2x - 8x^3 - 16x^4 = (1 + 2x)(1 - 2x + 4x^2) - 8x^3$
Therefore, the HCF is $1 - 2x + 4x^2$.